Virtual Reality Versus Monitor-Based Distraction in Children with Mild Intellectual Disability: A Preliminary Comparative Observational Study. - Fallea, Antonio; Treccarichi, Simone; L'Episcopo, Simona; Bartolone, Massimiliano; Vetri, Luigi; Vinci, Mirella; Ferri, Raffaele; Calì, Francesco (Children, 2026)
Background/Objectives: Dental anxiety represents a significant barrier to oral care in children with neurodevelopmental disorders (NDDs), whose sensory sensitivities and behavioral challenges often complicate clinical management and limit access to treatment. Virtual reality (VR) has emerged as a supportive tool to improve the feasibility of dental procedures in this vulnerable population. This study aims to evaluate whether a VR-based distraction approach could facilitate the completion of dental treatment in children with mild intellectual disability (ID). Methods: A prospective comparative observational study was conducted between February and September 2025 involving 56 children aged 11–15 years with mild ID and moderate dental anxiety (Corah Dental Anxiety Scale, DAS: 9–12). Participants were allocated to two groups of distraction approaches—VR distraction (n = 28) using the Oculus Quest 3® headset or a monitor-based cartoon (n = 28)—according to device availability and to maintain balanced group sizes. The primary outcome was treatment success, defined as completion of the restorative dental procedure under local anesthesia within 50 min. Results: Treatment success was achieved in 78.6% of the VR group versus 46.4% of the monitor group (p = 0.026). The odds of successful treatment were more than four times higher with VR compared to monitor distraction (OR 4.12; 95% CI: 1.16–16.47), with a risk ratio of 2.50 (95% CI: 1.14–5.50). Stratified analysis suggested a stronger effect in females (OR 12.25; 95% CI: 1.27–118.36) than in males (OR 2.56; 95% CI: 0.53–12.43). Conclusions: VR-based distraction significantly improved dental treatment success in children with mild ID compared with conventional distraction. Although gender differences were observed, they should be interpreted with caution due to the small sample size. This work lays the foundation for developing both short- and long-term protocols to facilitate dental treatment management and cooperation in patients with NDDs.